Long-Term Enrollment in Cardiac Rehabilitation Benefits of Cardiorespiratory Fitness and Skeletal Muscle Strength in Females with Cardiovascular Disease - Mike Pryzbek; Maureen MacDonald; Paul Stratford; Julie Richardson; Angelica McQuarrie; Robert McKelvie; Ada Tang (Mary Ann Liebert, 2021)
Background: The benefits of short-term cardiac rehabilitation (CR) for improving fitness are well known, but the effects of long-term maintenance-phase CR are less well established. Moreover, changes in cardiorespiratory fitness (CRF) and muscle strength with long-term CR have never been examined specifically in females, a population that is under-researched and under-represented in cardiovascular research. The objective of this retrospective pilot study was to estimate changes in CRF and muscle strength in females enrolled in a long-term CR program. Methods: Data from 39 females (mean???standard deviation age 65???9 years) enrolled for at least 1 year in a maintenance-phase CR program were analyzed. The program consisted of aerobic and resistance training, and data were collected annually for CRF (peak oxygen consumption [VO2peak, mL/kg/min]) and skeletal muscle strength (one-repetition maximum tests for chest press, seated row, and knee extension, kg). Mixed-model analyses were used to determine changes in CRF over the 5-year follow-up (203 observations) and muscle strength over 6 years (108 observations). Results: The CRF increased in females by 1.8%/year over 5 years of CR enrollment, and muscle strength increased by 0.6%?2.1%/year over 6 years. These findings are in contrast to the expected age-related declines in fitness over time. Conclusion: The positive long-term benefits on CRF and muscle strength in females provide initial preliminary support for maintenance-based CR, especially given that this population is commonly under-researched and under-represented in the CR literature.